A Different Path for Rural America. (May 2016) - Crabtree, John
Abstract: A dominant narrative in the United States posits that rural out‐migration and social decline of rural areas and small towns is inevitable. Although there is evidence of that view, there are also positive signs that point to the vitality of rural America. Although rural areas are losing population, that is partly a statistical artifact, since any rural area that succeeds in growing may be reclassified as an urban area, thus incorrectly seeming to indicate rural decline. This article explores three policy changes that could help to restore the vibrancy of rural and small‐town America: increased support for programs targeted toward rural economic development, setting limits on the ability of large farms to accrue a large share of the insurance subsidies available to farmers, and limiting the ability of vertically integrated hog farms to dissuade new farmers from investing in this traditional method of becoming a farmer.